Decluttering for enhanced workplace performance: The 5S solution - Rizky, Yulfani Akhmad; Khuzaini, Khuzaini; Shadiq, Syahrial (Center for Economics, Business and Entrepreneurship Development Faculty of Economics and Business, Universitas Muhammadiyah Malang, 2023)
Excessive clutter in the work environment can significantly hinder employee performance. The more items accumulate, the harder it becomes to maintain cleanliness, leading to a dirty and disorganized workspace. According to UCLA's Centre on Everyday Lives and Families, clutter can increase stress levels by elevating cortisol, which the brain interprets as a sign of failure. This stress reduces employees' cognitive abilities, further impacting their performance. Therefore, organizations must address this issue through decluttering. The 5S methodology—Seiri (Sort), Seiton (Set in order), Seiso (Shine), Seiketsu (Standardize), and Shitsuke (Sustain)—is an effective approach for decluttering and improving the work environment. This journal employs a literature review methodology, analyzing relevant sources such as previous journals, books, and articles. The review concludes that 5S is the most practical decluttering method for organizations. Various studies have demonstrated that 5S significantly enhances employee performance. Beyond performance improvements, 5S also boosts overall organizational efficiency, including time, energy, and cost savings.